Winter sports tribology: An experimental approach to understanding kinetic friction and equipment performance in speed skating - Hjelle, J. (Norwegian University of Science and Technology, 2017)
Friction behaviour in the sport of speed skating has been investigated by use of a tribometer designed at NTNU. The objective was to study if the tribometer could measure relative differences within different skate blades. Four aspects of friction behaviour have been studied: Load, width, surface treatment, and temperature, of the skate blade. A comparison between load and width, with respect to nominal contact pressure, has found a correlation between pressure and measured coefficient of friction. A correlation between different surface treatments of the skate blade has turned up inconclusive, and is suggested to be further evaluated with respect to poor reliability of results. Results obtained through the experiment, with respect to temperature of the skate blade and ice surface, have not displayed a clear correlation to the measured coefficient of friction. However, a significant increase in temperature for the skate blade displayed a higher coefficient of friction for the system. This temperature dependency correlates to previous research, suggesting an optimum temperature to exist between the two gliding interfaces.